Injection of Oxygenated Persian Gulf Water Into the Southern Bay of Bengal. Issue 14 (14th July 2020) - Sheehan, Peter M. F.; Webber, Benjamin G. M.; Sanchez‐Franks, Alejandra; Matthews, Adrian J.; Heywood, Karen J.; Vinayachandran, P. N.
Abstract: Persian Gulf Water (PGW) is an oxygenated, high‐salinity water mass that has recently been detected in the Bay of Bengal (BoB). However, little is known about the transport pathways of PGW into the BoB. Ocean glider observations presented here demonstrate the presence of PGW in the southwestern BoB. Output from an ocean reanalysis product shows that this PGW signal is associated with a northward‐flowing filament of high‐salinity water. Particle tracking experiments reveal two pathways: one in the eastern Arabian Sea that takes a minimum of 2 years and another in the western Arabian Sea that takes a minimum of 3 years. The western pathway connects to the BoB via equatorial currents. The greatest influx of PGW occurs between 82° and 87°E during the southwest monsoon. We propose that injection of PGW to the BoB oxygen minimum zone (OMZ) contributes to keeping oxygen concentrations in the BoB above the level at which denitrification occurs. Plain Language Summary: The Persian Gulf is a hot, shallow sea that acts like a vast salt pan. Consequently, water flowing out of the Gulf has a very high‐salt concentration; it also has a relatively high dissolved oxygen concentration. This high‐salt, high‐oxygen signal is distinct to Persian Gulf Water and is largely preserved as Persian Gulf Water spreads in the ocean's interior. In observations collected by an ocean glider, we identify the remnants of this high‐salt, high‐oxygen signal in the southwestern Bay of Bengal, a region that is notably lacking in dissolved oxygen. Using an ocean model, we identify two pathways taken by Persian Gulf Water between the northern Arabian Sea and the Bay of Bengal: one in the eastern Arabian Sea that takes a minimum of 2 years and one in the western Arabian Sea that takes a minimum of 3 years. Persian Gulf Water arrives in the Bay of Bengal throughout the year but particularly during the southwest monsoon (June to September). Persian Gulf Water brings oxygen to the Bay of Bengal and potentially plays a role in keeping dissolved oxygen levels in the bay above the level at which its ecological functioning would be significantly altered. Key Points: Persian Gulf Water injects oxygen into the Bay of Bengal oxygen minimum zone Two transport pathways exist: one in the eastern and one in the western Arabian Sea The flux of Persian Gulf Water into the Bay of Bengal is enhanced during the southwest monsoon